PENGENALAN EKONOMI DAN BISNIS ISLAM MELALUI PENCEGAHAN PENYEBARAN VIRUS COVID-19 DI KAMPUNG CENGAL, DESA KARACAK, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Rully Trihantana; Bayu Purnama Putra; Siti Fauziah (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The Covid-19 pandemic is a serious problem that must be addressed immediately. Prevention of the Covid-19 virus is something that must be carried out. Maintaining body stability is very important. Wearing masks, maintaining distance, and frequently washing hands are efforts to minimize transmission of the virus between humans. This community service is an effort to help the community to prevent, break the chain of spread of the Covid-19 virus, increase the resilience of the community in their own village to be alert, alert so that it becomes a resilient village facing the Covid-19 outbreak. This was carried out by spraying disinfectants, counseling on prevention of the Covid-19 virus, education on making masks from tissue paper, distributing cloth masks, and healthy exercise. At the same time, the community was also introduced to Islamic economics and business. The community service activities which run from July to August 2020 are located in Cengal Village, Karacak Village, Leuwiliang District, Bogor Regency. The success of this activity can be seen from the enthusiasm of the community.